Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 125668 by mnjuly1970 last updated on 12/Dec/20

                ... advanced  calculus...       evaluate:::           Φ=∫_0 ^( (π/4)) ln(ln(cot(x)))dx=?

...advancedcalculus...evaluate:::Φ=0π4ln(ln(cot(x)))dx=?

Answered by mindispower last updated on 13/Dec/20

Φ=∫_1 ^∞ ((ln(ln(x)))/(1+x^2 ))dx=∫_0 ^∞ ((ln(t))/(1+e^(2t) ))e^t dt  =∫_0 ^∞ ((ln(t)e^(−t) )/(1+e^(−2t) ))dt  =Σ_(k≥0) ∫_0 ^∞ (−1)^k ln(t)e^(−(1+2k)t)   ln(t)=∂_s t^s ∣s=0  g(s)=Σ_(k≥0) ∫_0 ^∞ (−1)^k t^s e^(−(1+2k)t) dt  =Σ_(k≥0) ∫_0 ^∞ (−1)^k ((y^s e^(−y) dy)/((1+2k)^(s+1) ))  =Σ_(k≥0) (((−1)^k )/((1+2k)^(s+1) ))∫_0 ^∞ y^s e^(−y) dy  =Σ_(k≥0) (((−1)^k )/((1+2k)^(s+1) ))Γ(s+1)  =Γ(s+1)Σ_(k≥0) ((1/((1+4k)^(s+1) ))−(1/((3+4k)^(s+1) )))  =((Γ(s+1))/4^(s+1) )(Σ_(k≥0) (1/((k+(1/4))^(s+1) ))−Σ_(k≥0) (1/((k+(3/4))^(s+1) )))  =((Γ(s+1))/4^(s+1) )(ζ(s+1,(1/4))−ζ(s+1,(3/4))  ζ(s,q)=Σ_(n≥0) (1/((n+q)^s )),Zets hrwitz function  we want g′(0)  ((Γ′(s+1)4^(s+1) −4^(s+1) ln(4)Γ(s+1))/4^(2s+2) )∣_(s=0) .lim_(s→0) (ζ(s+1,(1/4))−ζ(s+1,(3/4)))  +lim_(s→0) ∂_s (ζ(s+1,(1/4))−ζ(s+1,(3/4))).((Γ(s+1))/4^(s+1) )  ζ(s+1,q)=(1/s)+Σ(((−1)^n )/(n!))γ_n (q)s^n ,laurent serie  expansion γ_n (q) Stieltjes constante  ζ(s+1,(1/4))−ζ(s+1,(3/4))=h(s)=Σ_(n≥0) (((−1)^n )/(n!))(γ_n ((1/4))−γ_n ((3/4)))s^n   lim_(s→0) h(s)=γ_0 ((1/4))−γ_0 ((3/4))  ∂_s h(s)=Σ_(n≥1) (((−1)^n )/((n−1)!))(γ_n ((1/4))−γ_n ((3/4))s^(n−1)   lim_(s→0) h′(s)=γ_1 ((3/4))−γ_1 ((1/4))  γ_1 ((3/4))−γ_1 (1−(3/4))=2πΣ_(l=1) ^3 sin(((6πl)/4))lnΓ((l/4))−π(γ+ln(8π))cot(((3π)/4))  =−2πΓ((1/4))+2πΓ((3/4))+π(γ+ln(8π))  =2π(Γ((3/4))−Γ((1/4)))+π(γ+ln(8π))  γ_0 ((1/4))−γ_0 ((3/4))=Ψ((3/4))−Ψ((1/4))=−πcot(((3π)/4))  =π  g′(0)=((4Γ′(1)−4ln(4)Γ(1))/4^2 )π+(2π(Γ((3/4))−Γ((1/4)))+π(γ+ln(8π)).(1/4)      =−(γ/4)π−((ln(2))/2)π+(π/2)(Γ((3/4))−Γ((1/4)))+((γπ)/4)+(π/4)ln(8π)  =(π/4)ln(2π)+(π/2)(Γ((3/4))−Γ((1/4)))

Φ=1ln(ln(x))1+x2dx=0ln(t)1+e2tetdt=0ln(t)et1+e2tdt=k00(1)kln(t)e(1+2k)tln(t)=stss=0g(s)=k00(1)ktse(1+2k)tdt=k00(1)kyseydy(1+2k)s+1=k0(1)k(1+2k)s+10yseydy=k0(1)k(1+2k)s+1Γ(s+1)=Γ(s+1)k0(1(1+4k)s+11(3+4k)s+1)=Γ(s+1)4s+1(k01(k+14)s+1k01(k+34)s+1)=Γ(s+1)4s+1(ζ(s+1,14)ζ(s+1,34)ζ(s,q)=n01(n+q)s,Zetshrwitzfunctionwewantg(0)Γ(s+1)4s+14s+1ln(4)Γ(s+1)42s+2s=0.lims0(ζ(s+1,14)ζ(s+1,34))+lims0s(ζ(s+1,14)ζ(s+1,34)).Γ(s+1)4s+1ζ(s+1,q)=1s+Σ(1)nn!γn(q)sn,laurentserieexpansionγn(q)Stieltjesconstanteζ(s+1,14)ζ(s+1,34)=h(s)=n0(1)nn!(γn(14)γn(34))snlims0h(s)=γ0(14)γ0(34)sh(s)=n1(1)n(n1)!(γn(14)γn(34)sn1lims0h(s)=γ1(34)γ1(14)γ1(34)γ1(134)=2π3l=1sin(6πl4)lnΓ(l4)π(γ+ln(8π))cot(3π4)=2πΓ(14)+2πΓ(34)+π(γ+ln(8π))=2π(Γ(34)Γ(14))+π(γ+ln(8π))γ0(14)γ0(34)=Ψ(34)Ψ(14)=πcot(3π4)=πg(0)=4Γ(1)4ln(4)Γ(1)42π+(2π(Γ(34)Γ(14))+π(γ+ln(8π)).14=γ4πln(2)2π+π2(Γ(34)Γ(14))+γπ4+π4ln(8π)=π4ln(2π)+π2(Γ(34)Γ(14))

Commented by mindispower last updated on 13/Dec/20

we can   use Γ(z)Γ(z+(1/2))=2^(1−2z) (√π)Γ(2z)  Γ((1/4)).Γ((3/4))=2^(1/2) (√π).Γ((1/2))=π(√2)  ⇒Γ((3/4))=π(√2).(1/(Γ((1/4))))...to express using  just Γ((1/4))

wecanuseΓ(z)Γ(z+12)=212zπΓ(2z)Γ(14).Γ(34)=212π.Γ(12)=π2Γ(34)=π2.1Γ(14)...toexpressusingjustΓ(14)

Commented by mnjuly1970 last updated on 13/Dec/20

thanks alot   mr power......

thanksalotmrpower......

Commented by mindispower last updated on 13/Dec/20

withe pleasur

withepleasur

Terms of Service

Privacy Policy

Contact: info@tinkutara.com